Gambaran Kesejahteraan Psikologis Pemulung di Kampung Pemulung Cilandak - Laurentius Purbo Christianto; Victoria Puteri Arista; Alfonsus Sanders; Anggun Karisma Megawati; Marcellino Pierre Yoga; Surya Artha (Fakultas Psikologi Universitas Sanata Dharma, 2021)
Scavenging is an activity that contains collecting and sell or trade garbage with money. Scavenger or waste pickers is a person who did that kind of activity. In Indonesia, it is estimated that there are 5 million scavengers. They belong to the low-income economic group. Scavengers generally live in a scavenger village. Scavenger villages generally smell like garbage, have poor sanitation, look untidy, there are small semi-permanent houses, and there are health issues that threaten the residents. Economic conditions and poor living environment can have an impact on the psychological well-being of scavengers.It is important to research more deeply into the psychological well-being of scavengers. The results of the research can be used as material for policy making for the government, and for making assistance programs for social communities who assist scavengers. This research can also be seen as an effort to help scavengers (as marginal groups) to voice themselves.This research is focused on descripting psychological well-being of scavengers who live in Cilandak scavenger village, in Jakarta, Indonesia. The research uses a qualitative approach with a narrative design. The research participants were 3 scavengers (2 male and 1 female). Data was collected by semi-structured interviews. The results showed that the three participants in the domain of autonomy and environmental control had not been able to fulfill it properly, because their work and village were controlled by other people. In the domain of life goals, self-acceptance, personal development, and positive relationships with others, the three participants had different situations.